2019
DOI: 10.3389/fimmu.2019.00371
|View full text |Cite
|
Sign up to set email alerts
|

Human TLR8 Senses RNA From Plasmodium falciparum-Infected Red Blood Cells Which Is Uniquely Required for the IFN-γ Response in NK Cells

Abstract: During blood-stage malaria, the innate immune system initiates the production of pro-inflammatory cytokines, including IFN-γ, that are critical to host defense and responsible for severe disease. Nonetheless, the innate immune pathways activated during this process in human malaria remain poorly understood. Here, we identify TLR8 as an essential sensor of Plasmodium falciparum -infected red blood cells (iRBC). In human immune cells, iRBC and RNA purified from iRBC were detected by TLR8 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 77 publications
4
35
0
Order By: Relevance
“…Ligands for some TLRs like TLR2 (di-or triacetylated lipopeptides) and TLR4 (lipopolysaccharide, LPS) prime monocytes for IL-1β production (i.e., induce pro-IL-1β); however, IL-1β secretion requires additional inflammasome activation, e.g., by the bacterial toxin nigericin [17]. In contrast, IL-1β (and TNF-α) secretion can be stimulated by TLR8 ligands in human monocytes also in a caspase-1 independent pathway [19,20]. Importantly, inflammasome activation in monocytes triggers pyroptosis, a highly inflammatory form of programmed cell death [21].…”
Section: Introductionmentioning
confidence: 99%
“…Ligands for some TLRs like TLR2 (di-or triacetylated lipopeptides) and TLR4 (lipopolysaccharide, LPS) prime monocytes for IL-1β production (i.e., induce pro-IL-1β); however, IL-1β secretion requires additional inflammasome activation, e.g., by the bacterial toxin nigericin [17]. In contrast, IL-1β (and TNF-α) secretion can be stimulated by TLR8 ligands in human monocytes also in a caspase-1 independent pathway [19,20]. Importantly, inflammasome activation in monocytes triggers pyroptosis, a highly inflammatory form of programmed cell death [21].…”
Section: Introductionmentioning
confidence: 99%
“…However, this TLR8-TLR13 equivalency only applies to pathogens containing the TLR13 consensus sequence. TLR8 also senses plasmodia RNA in humans, ( Coch et al., 2019 ), which activates TLR7, not TLR13 in mice. Indeed, how TLR8 senses non-self RNA is an unresolved question.…”
Section: Main Textmentioning
confidence: 99%
“…Meanwhile, the relationship between TLR8 and autoimmune diseases has received considerable attention (Farrugia & Baron, 2017), with well known examples including systemic lupus erythematosus (Devarapu & Anders, 2018) and rheumatoid arthritis (Elshabrawy et al, 2017). Since TLR8 (and TLR7) senses and responds to various kinds of RNA viruses (Marcken et al, 2019;Coch et al, 2019), TLR8 deficiency has been proposed to cause viral infections; however, it has been reported that TLR8 deletion accelerates autoimmunity in mice (Tran et al, 2015).…”
Section: Tlr8 As a Therapeutic Targetmentioning
confidence: 99%